Prevalence of skin disorders in HIV infected children and their association with CD4 count. (4th April 2011) - Bandi, S; Flutter, L; Hackett, S; Welch, S; Reyburn, H
Abstract : Background: Skin disorders are common in HIV infection, even where the condition has not yet progressed to full-blown AIDS. The impact of Anti Retro Virals (ARV) on these manifestations is not clear although multiple anecdotal reports suggest a close relationship between CD4, ARV and the prevalence of skin disorders. Our main objectives were to estimate the prevalence of skin disorders in children with HIV, the relationship between immune status and skin disorders and whether HAART modified the prevalence of skin disorders. Methods: This was a retrospective study of case-notes where the unit of the study was the record of a single consultation. Data were collected from all HIV positive children currently in follow-up at the clinic. Case notes were used to determine the CD4 and treatment status, and diagnostic record of skin conditions. Skin conditions were assumed to continue until case notes indicated their resolution or change. Statistical analysis included the use of linear regression to determine independent effects of risk factors for the presence of skin disease. Results: 75 children under follow-up in the HIV clinic were included in the study. The median age at the time of diagnosis of skin disease was 10.88 years; 32/34 (94%) were of African origin, one child was white British and another was of Southeast Asian origin. Overall 34/75, (45%, CI 34.06 – 56.6%) children had a skin diagnosis recorded and among 118 consultations, 80 (67%) were accompanied by a record of skin diagnosis. Eczema and skin infections were the most common skin disorders. HAART, age or sex had no independent association with skin disorders, whereas a CD4% >20% was associated with a reduced odds of skin disease (OR 0.44, 95% CI 0.21 to 0.91). Conclusion: Skin disorders in HIV infected children are common; the prevalence in our study was 45%. CD4 levels were negatively associated with the presence of skin disorders and this was particularly true of children who were not on HAART. There was no evidence of an independent effect of HAART on skin disorders.